Macrophages hit a nerve in painful joint venture: Neuroimmunology - Ben Brahim, Oumaima; Uderhardt, Stefan (Nature Reviews Rheumatology, 2025)
Hasegawa et al. reveal how synovial joints detect systemic inflammation through specialized fenestrated blood vessels at the synovial periphery. Three distinct macrophage populations and nociceptor neurons form a sentinel unit around these vessels, coordinating immune responses and pain signalling through interleukin-1β (IL-1β) and calcitonin gene-related peptide (CGRP) signalling.
CRIS-Team Scopus Importer:2025-03-07